2016
DOI: 10.3390/ijms17030301
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Connexin26 in the Mature Cochlea Increases Susceptibility to Noise-Induced Hearing Loss in Mice

Abstract: Connexin26 (Cx26, encoded by GJB2) mutations are the most common cause of non-syndromic deafness. GJB2 is thought to be involved in noise-induced hearing loss (NIHL). However, the role of Cx26 in NIHL is still obscure. To explore the association between Cx26 and NIHL, we established a Cx26 knockdown (KD) mouse model by conditional knockdown of Cx26 at postnatal day 18 (P18), and then we observed the auditory threshold and morphologic changes in these mice with or without noise exposure. The Cx26 KD mice did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Recently, a study found that both Cx26 and Cx30 protein levels were significantly decreased after noise exposure (Yamaguchi et al, 2014). Since then, another study has shown that when Cx26 is conditionally knocked down at postnatal day 18, mice exhibit more pronounced noise-induced hearing loss than their wildtype (WT) counterparts (Zhou et al, 2016). At present, it is unknown whether patients harbouring GJA1 mutations are more susceptible to auditory damage after a loud noise exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study found that both Cx26 and Cx30 protein levels were significantly decreased after noise exposure (Yamaguchi et al, 2014). Since then, another study has shown that when Cx26 is conditionally knocked down at postnatal day 18, mice exhibit more pronounced noise-induced hearing loss than their wildtype (WT) counterparts (Zhou et al, 2016). At present, it is unknown whether patients harbouring GJA1 mutations are more susceptible to auditory damage after a loud noise exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Humans with the V84L mutation in Cx26, which has intact junctional conductance but absent transmission of IP 3 , a Ca 2+ second messenger necessary for ICS activity, have hearing loss [18], suggesting that ICS activity is protective and its disruption central to the pathogenesis of Cx26-associated hearing loss. Finally, a recent study showed that Cx26 conditional knockout mice have increased susceptibility to noise-induced hearing loss, suggesting a common pathophysiologic mechanism underlying both forms of deafness [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Burke et al and Kim et al a heterozygote ratio increases with normal hearing in a group with sensory hearing loss compared to the control group [26,27]. In rats, reduced expression of connexin 26 after 18 days of birth has increased the susceptibility of Corti's normal organ to acoustic trauma and degenerative lesions [28]. Van Eyken and his friends work.…”
Section: Resultsmentioning
confidence: 98%